Outcome of the 1st International Biological Nitrification Inhibition (BNI) Workshop - Japan International Research Center for Agricultural Sciences (2015)
Suppressing soil nitrification and increasing NUE is critical to reversing the N-fertilizer overuse and minimizing its environmental impact. Global nitrogen (N) fertilizer consumption has increased >10-fold since 1960s, but food grain production has only tripled during this period, resulting in a decrease in nitrogen-use efficiency (NUE). Of the 150 million tons of N-fertilizer currently applied to agricultural systems globally, up to 70% is not recovered by the crop and often results in negative environmental impact through pathways such as nitrate-leaching and nitrous oxide emissions1. Nitrate is an important groundwater pollutant and nitrous oxide (N2O) is a powerful greenhouse gas. Annual economic losses from lost N-fertilizer is estimated at 90 US$ billion. If this trend continues, annual N-fertilizer application will double by 2050 and global N2O emissions from agriculture will reach 19 million tons of N y-1 by then.